1999
DOI: 10.1038/sj.mp.4000477
|View full text |Cite
|
Sign up to set email alerts
|

Association between a marker in the UCP-2/UCP-3 gene cluster and genetic susceptibility to anorexia nervosa

Abstract: Anorexia nervosa (AN) is an enigmatic syndrome affecting approximately 0.1% of the at risk population in the UK which equates to approximately 70 000 sufferers. Data from a number of studies have demonstrated the heritability of this disorder, however it is only in the last few years that studies have begun to determine the involvement of particular candidate genes in this genetic predisposition. In the current study we have used classical case-control association analysis to determine whether two highly polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 10 publications
2
18
0
1
Order By: Relevance
“…The distribution of alleles we found for D11S916 was similar to that observed by Campbell et al, 7 but D11S911 was markedly different. Campbell et al reported 17 alleles whereas we found 19, ranging from 159 bp to 215 bp on 666 chromosomes.…”
Section: Analysis Of Microsatellite Markers At the Ucp2/ucp3 Locus Onsupporting
confidence: 74%
See 2 more Smart Citations
“…The distribution of alleles we found for D11S916 was similar to that observed by Campbell et al, 7 but D11S911 was markedly different. Campbell et al reported 17 alleles whereas we found 19, ranging from 159 bp to 215 bp on 666 chromosomes.…”
Section: Analysis Of Microsatellite Markers At the Ucp2/ucp3 Locus Onsupporting
confidence: 74%
“…Campbell et al 7 reported allelic association between a microsatellite marker at the UCP2/UCP3 locus on chromosome 11q13 and anorexia nervosa. Resting metabolic rate (RMR) is linked to the uncoupling protein 2/3 (UCP2/3) locus on chromosome 11q13 8 and polymorphisms within UCP2 are associated with metabolic rate.…”
Section: Analysis Of Microsatellite Markers At the Ucp2/ucp3 Locus Onmentioning
confidence: 99%
See 1 more Smart Citation
“…A linkage to this locus was also observed in patients with anorexia nervosa [193]. Kaisaki et al [155] localized the UCP2 and UCP3 genes to a region of rat chromosome 1 linked to glucose intolerance and adiposity in the Goto-Kakizaki type II diabetic rat.…”
Section: Linkage and Association Studies Of Human Ucp Genesmentioning
confidence: 92%
“…For example, an association between a specific polymorphism in the uncoupling proteins UCP-2/UCP-3 gene cluster and anorexia nervosa has been described. 11 The aim of our study was to analyze the function of energetic metabolism in females with anorexia nervosa directly by the measurement of activities of respiratory chain complexes in isolated platelets.…”
Section: Introductionmentioning
confidence: 99%